Islamic Banking Opportunities Across Small and Medium Enterprises : Pakistan - International Finance Corporation (International Finance Corporation, Cairo, 2017)
In recent years, banks in Pakistan and the Middle East and North Africa (MENA) region have become increasingly interested in targeting the small and medium enterprise (SME) sector and have realized that many small businesses demand Shariah-compliant banking. To provide clarity on the subject, International Finance Corporation (IFC) commissioned a study to better understand the demand and supply for Islamic banking products (both asset and liability products as well as other banking services) in the SME sector in Pakistan. This report on Pakistan reveals a new to bank Islamic funding and depository opportunity, primarily due to un-served and underserved SMEs (approximately 20 percent to 25 percent), who do not borrow from conventional banks due to religious reasons. In order to reach out to SMEs demanding Islamic products, and as part of IFC’s initiative to enhance its SME investment and advisory services offerings to Islamic financial institutions, one needed to better understand the market from both the demand and supply sides in order to identify any gaps or niches where IFC can assist and add value. IFC commissioned a study in nine countries of the MENA region, which includes Pakistan, to better understand the demand and supply for Islamic banking products (both asset and liability products and other banking services) in the SME sector. The countries chosen for this study are: (1) Iraq, (2) Pakistan, (3) Yemen, (4) Kingdom of Saudi Arabia, (5) Egypt, (6) Lebanon, (7) Morocco, (8) Tunisia, and (9) Jordan. This regional executive summary provides a comparative analysis of the SME potential across these countries and the opportunities available to Islamic institutions to tap this potential. The nine individual country reports provide a deeper insight into the SME landscape and potential opportunities for Islamic banks in each country. The reports also highlight the measures that banks may need to take to successfully target the Islamic banking potential of SMEs. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.